Organizational Support and Work Engagement Factor for the Implementation of Mh02 Technology with the Delone Mclean Model - Pranugroho, Bagus; Miftachudin, Miftachudin; Bakti, Aprian Krisna; Syamil, Ahmad (LPPM of NAROTAMA UNIVERSITY, 2023)
In the implementation of a system, if the organization provides support to employees for their tasks, the employees will enjoy their work and improve performance through the use of the new system. In addition, when employees feel the same connection with their job or workplace. In mining activities, operators have the potential for high levels of fatigue because production activities are carried out 24 hours and are divided into 2 shifts. In anticipation of accidents caused by fatigue, PT Pamapersada Nusantara is currently developing technology in the unit cabin that can detect indications of operator fatigue when operating the unit. The technology in question is DMS/MH02 (Driving Monitoring System / Mata Hati 2). This research proposes to examine the role of organizational support ,work engagement between and MH02 technology in coal mining use Delone & Mclean model. The quantitative research technique is referred to as the research method. The target of this research is PT. Pamapersada Nusantara, and the research sample, which consists of 279 respondents, refers to the structural equational modelling model. From the results of the research that has been carried out, it turns out that DMS/MH02 for user satisfaction, net benefit, use from user perceptions expressed agreement regarding usability, satisfaction and usefulness for the average value of usability (DMS/MH02 use) at 3.6 while for usefulness ( net benefit) with an average of 4 and for user satisfaction it has the lowest average value, namely 3.27.For the role of organizational support in the implementation of DMS/MH02, it is proven to have a positive influence on DMS/MH02 use. The study found that there was a statistically significant effect of technical and organizational variables in management information system applications. This study led to the need to involve employees and users in the planning process for developing the information/technology system.